Chronic Immune Activation and CD4+ T Cell Lymphopenia in Healthy African Individuals: Perspectives for SARS-CoV-2 Vaccine Efficacy - Wolday, Dawit; Ndungu, Francis M.; Gómez-Pérez, Gloria P.; de Wit, Tobias F. Rinke (Frontiers in Immunology, 2021)
Chronic immune activation has been considered as the driving force for CD4+ T cell depletion in people infected with HIV-1. Interestingly, the steady immune profile of adult HIV-negative individuals living in Africa also exhibit chronic immune activation, reminiscent of that observed in HIV-1 infected individuals. It is characterized by increased levels of soluble immune activation markers, such as the cytokines IL-4, IL-10, TNF-α, and cellular activation markers including HLA-DR, CD-38, CCR5, coupled with reduced CD45RA+ (naïve) and increased CD45RO+ (memory cells) in CD4+ and CD8+ subsets. In addition, it is accompanied by low CD4+ T cell counts when compared to Europeans. There is also evidence that mononuclear cells from African infants secrete less innate cytokines than Sound and North Americans and Europeans in vitro. Chronic immune activation in Africans is linked to environmental factors such as parasitic infections and could be responsible for the previously observed immune hypo-responsiveness to infections and vaccines. It is unclear whether the immunogencity and effectiveness of anti-SARS-CoV-2 vaccines will also be reduced by similar mechanisms. A review of studies investigating this phenomenon is urgently required as they should inform the design and delivery for vaccines to be used in African populations.